Biotin as a masking agent in chorionic gonadotropin assays utilizing biotinylated antibodies. Issue 11 (27th August 2021) - Sobolevsky, Tim; Ahrens, Brian
Abstract: Biotin interference in streptavidin/biotin‐based immunoassays has been recently recognized as a confounding factor in clinical settings. Depending on the nature of the assay, the presence of excess biotin in patient samples can cause falsely high or low results. One of the platforms known to be affected, Roche Cobas, is widely used in anti‐doping laboratories to test for intact chorionic gonadotropin (hCG) in urine. While biotin levels in blood have been well studied, less is known about urinary biotin due to its limited clinical significance. Having analyzed over 4, 000 urine samples, we have established a reference range for urinary biotin with a median concentration of approximately 12 ng/ml. However, a significant number of samples contain much higher amounts, with a maximum approaching 10 μg/ml, suggesting biotin supplementation. Consequently, the tolerance of hCG STAT assay towards biotin was investigated over a wide concentration range. The apparent hCG concentration was found to decrease almost linearly as biotin increased from 100 to 1, 000 ng/ml, with only 10% of the expected value reported by the assay as biotin reached 1, 000 ng/ml. Further increase of biotin resulted in a progressive, albeit more moderate, decline in measured hCG concentration. To avoid a false negative result in the context of anti‐doping analysis, it is highly recommended to monitor biotin in urine and perform diafiltration before hCG measurement in samples with elevated biotin to remove the interference. Abstract : Tolerance of hCG STAT asssay towards biotin was investigated. The apparent hCG concentration was found to decrease almost linearly as biotin increased from 100 to 1, 000 ng/ml, with only 10% of the expected value reported by the assay as biotin reached 1, 000 ng/ml. To avoid a false negative result in the context of anti‐doping analysis, it is recommended to monitor biotin in urine and perform diafiltration before hCG measurement in samples with elevated biotin to remove the interference.